Suillus placidus Singer, Farlowia 1945 - Palamarchuk, Marina A.; Kirillov, Dmitry V.; Shadrin, Dmitry M. (Zenodo, 2021)
Suillus placidus (Bonord.) Singer, Farlowia 2 (1): 42 (1945) (Figs. 3 c, d) Pileus 30–100 mm in diam., rounded-convex to plane, viscid to slimy, white, pale-yellow, grey-white, sometimes irregularly colored in brown tints, brown in the center, white on the edges or with brown or grayish stripes or spots. The cuticle is easily removed to the center. Tubes and pores pale-yellow, yellow, from lemon yellow to yellow-brown, adnate or slightly decurrent. Stipe 40–120 mm length, 10–23 mm width, white, yellow in upper part, all covered with small dark-brown glandular dots. Flesh white, slightly yellowish. Smell tarry. Basidia 20–25 × 6–7 μm, cylindrical, clavate, 4-spores. Basidiospores 7–9 × (2.5)3–3.5 μm, Q = 2.0–2.9, fusiform, yellowish-olive. Cheilo - and pleurocystidia 34–52 × 7–12 μm, cylindrical or slightly swollen at the ends, hyaline or with dark-brown content, fasciculate. Pileipellis ixotrichoderm, consisting of intertwined hyphae of 2–7 μm width, immersed in gelatinous substance. Caulocystidia like pleuro- and cheilocystidia, cylindrical, fusiform, clavate, with brown content, fasciculate. Clamp connections absent in all tissues. Ecology and distribution . The species has a Holarctic areal and forms ectomycorrhizae with Pinus : in Europe (Alps)—with Pinus cembra in Siberia and Far East—with P. sibirica , P. koraiensis , P. pumila in India —with P. wallichiana A. B. Jacks (1938: 85); in China —with P. massoniana Lamb. (1803: 12); in North America—with P. strobus (Smith & Thiers 1964; Munoz 2005; Verma & Reddy 2016). In Russia, the species was found in Far East (Vasilyeva 1973), Siberia (Perova & Gorbunova 2001; Zvyagina & Baykalova 2012) and the Urals (Perevedentseva 2008; Palamarchuk 2012; Degteva 2019). It occurs solitary or gregarious. Collection examined . RUSSIA, Troitsko-Pechorsky district, Pechoro-Ilychsky Nature Reserve: the Mountain Medvezhiy Kamen, 62°04’22.3”N, 59°04’39.0”E, spruce green moss forest with Pinus sibirica, 10 Aug. 2004, col. M. Palamarchuk , SYKOf 239; 6 km upstream the Pechora River from cordon Shezhym-Pechorsky, 62°03’39.2”N, 58°28’4.1”E, spruce green moss-sphagnum forest with Pinus sibirica , 30 Jul. 2004, col. M. Palamarchuk , SYKOf 240; near the settlement Yaksha, 61°49’31.1”N, 56°50’40.7”E, spruce green moss forest with Pinus sibirica , 31 Aug. 2011, col. M. Palamarchuk , SYKOf 1816; the Ridge Poyasoviy Kamen, head of the Pechora River, 62°13’21.0”N, 59°24’0.1”E, mountain spruce herbal forest with Pinus sibirica , 05 Aug. 2018, col. M. Palamarchuk , SYKOf 2968. Vuktyl district, “Yugyd va” National Park: basin of the Schugor River, Nizhnie Vorota, left bank, 2 km upstream, 64°12’45.1”N, 57°59’45.3”E, spruce green moss forest with Pinus sibirica , 10 Aug. 2016, col. M. Palamarchuk , D. Kirillov , SYKOf 2595, 2664; ibid., 14 Aug. 2016, col. M. Palamarchuk , D. Kirillov , SYKOf 2665; the same location, 64°12’43.2”N, 57°59’51.6”E, spruce green moss forest with Pinus sibirica , 26Aug. 2018, col. M. Palamarchuk , SYKOf 2912; basin of the Podcherem River, 63°30’52.1”N, 58°37’22.0”E, spruce green moss forest with Pinus sibirica , 04 Aug. 2017, col. M. Palamarchuk , SYKOf 2737. Note. Suillus placidus can be recognized by the white or white-brown pileus, absent ring and dark-brown glandular dots on stem. In most of the identification guides, the pileus of S. placidus is white, becoming slightly yellowish over time (Smith & Thiers 1964; Munoz 2005). The glutinous layer of old basidiomata can become gray in wet weather (Smith & Thiers 1964). Some of the specimens collected by us in the study area had a white pileus, typical of this species, and the pileus of some of them was brown. Similar specimens of S. placidus with brown pileus were noted in West Siberia (Filippova 2019). Literature survey showed that the specimens from Korea were also demonstrated the color of pileus, varying from white to brown (Min et al. 2014). Molecular analysis also revealed the highest similarity of our specimens of S. placidus with those from Asia. Specimens of Suillus placidus with brown pileus are similar to S. subalpinus , but the latter is recorded only in mountains of North America. : Published as part of Palamarchuk, Marina A., Kirillov, Dmitry V. & Shadrin, Dmitry M., 2021, Morphology and molecular data of the species of Suillus (Suillaceae, Boletales) associated with Pinus sibirica at the European northeast of Russia, pp. 18-34 in Phytotaxa 490 (1) on pages 28-29, DOI: 10.11646/phytotaxa.490.1.2, http://zenodo.org/record/5756712 : {"references": ["Smith, A. H. & Thiers, H. D. (1964) A contribution toward a monograph of North American species of Suillus (Boletaceae). Ann Arbor, Michigan. 163 pp.", "Munoz, J. A. (2005) Boletus s. l. Fungi Europaei 2. Edizioni Candusso, Alassio. 820 pp.", "Verma, B. & Reddy, M. S. (2016) Diversity of the genus Suillus Gray from coniferous forests of the northwestern Himalayas, India: Taxonomy, ecology and some newrecords. Kavaka 47: 114 - 124.", "Vasilyeva, L. N. (1973) Mushrooms (Agaricales) of the Primorsky Kray. Nauka, Leningrad. 331 pp. [In Russian]", "Perova, N. V. & Gorbunova, I. A. (2001) Macromycetes of south of the Western Siberia. Izdatelstvo SO RAN, Novosibirsk. 158 pp. [In Russian]", "Zvyagina, E. A. & Baykalova, A. S. (2012) Preliminary data on the mycobiota of the agaricoid basidiomycetes of the Surgut Polesie. In: Man and the North: anthropology, archeology, ecology. Vol. 2: Proc. All-Russ. conf. Tyumen, pp. 343 - 346. [In Russian]", "Perevedentseva, L. G. (2008) Synopsis of agaricoid basidiomycetes of the Perm Krai. Perm State Pedagogical University, Perm. 86 pp. [In Russian]", "Palamarchuk, M. A. (2012) Agaricoid basidiomycetes of the Pechoro-Ilychsky Nature Reserve (Northern Urals). Syktyvkar. 152 pp. [In Russian]", "Degteva, S. V. (2019) The Red Data Book of the Komi Republic. Komi Republican Printing House, Syktyvkar. 768 pp.", "Filippova, N. (2019) The Fungarium of Yugra State University reference collection. Version 1.7. Yugra State University Biological Collection (YSU BC). [Occurrence dataset https: // doi. org / 10.15468 / g 4 bk 6 h accessed via GBIF. org on 2019 - 11 - 26. https: // www. gbif. org / occurrence / 2397822374]", "Min, Y. J., Park, M. S., Fong, J. J., Seok, S. J., Han, S-K. & Lim, Y. W. (2014) Molecular Taxonomical Re-classification of the Genus Suillus Micheli ex S. F. Gray in South Korea. Mycobiology 42 (3): 221 - 228. https: // doi. org / 10.5941 / MYCO. 2014.42.3.221"]}